The Spatial Management System in Poland: The Categorisation of the Problem from the Perspective of the Literature on the Subject - Nowak, Maciej (Journal of Public Governance, 2021)
Objectives: The article aims to distinguish institutional assessments of the Polish spatial management system’s weaknesses in the literature on the subject, as well as place them in the context of the international discussion and the hsistorical context.Research Design & Methods: The article diagnoses the defects of the spatial management system in Poland, published in 2010–2020, which were confronted with the current theses concerning spatial management systems in Europe and those related to the spatial management system in the Polish People’s Republic before 1989. Based on this, the recurring problems and the key challenges for the Polish spatial management system have been identified.Findings: One can consider the correctness of the assumption that the system in spatial management (considering historical and social conditions and differences, etc.) was less developed than the current one, adopted in Poland after 1989. On the other hand, the solutions adopted in some Western European countries can be considered as much betterprepared than those in Poland (the basis for such a thesis is the enormous spatial chaos generating serious costs, which was indicated in the Polish literature on the subject to a much greater degree than in other countries).Implications / Recommendations: There should be a wider interdisciplinary connection and coherence of the expressed assessments, as well as a wider consideration of Western European countries’ experience.Contribution / Value Added: The article offers a critical analysis of the literature on the subject concerning spatial management in Poland, proposing new research directions and referencing the literature from the Polish People’s Republic, as well as literature on spatial management systems in other European countries.Article classification: review article – original literature reviewJEL classification: R11